Les recettes de cuisine dans Châtelaine : des indices d’évolution au regard des normes du bien manger (1960 à 2009) - Jean-Philippe Laperrière (Communiquer)
In the 20th century of Quebec, the mass media producing especially the women’s press. This is very important to transmit to families the ways of doing things in a growing new society. Moreover, the media are often perceived as important norms vectors and behaviors. For us, food practices are more the product of representations of these norms and mass media can produce them. It is for this reason then the cooking recipes of chronicles of Châtelaine, the oldest magazine of its kind, are studied. We want to know how, through simple representations, they transpose the healthy eating recommendations published by the Canadian government. Our analyzes show that cooking recipes transpose recommendations, but also other norms, which are more social and are linked to lifestyles encouraged by the bourgeoisie of modern societies.